PREVALENCE OF TOOTH DECAY AND OHI-S VALUES IN ELEMENTARY SCHOOL CHILDREN AFTER THE ERUPTION OF SEMERU IN SUMBERMUJUR VILLAGE, LUMAJANG - Trining Widodorini; Agustine Hanafi Putri; Latifah Fitriani Rakhman; Rahmavidyanti Priyanto; Lalita El Milla (Caring : Jurnal Pengabdian Masyarakat, 2023)
Mount Semeru in Lumajang-East Java erupted on Saturday 4 December 2021 at 15.15 WIB and affected 12 villages. One of the impacts caused by the eruption of Mount Semeru is the decline in the quality of life of the population seen from the health problems that arise, both general health and dental and oral health. The purpose of community service is to determine the prevalence of tooth decay and OHI-S score in elementary school children after the eruption of Semeru in Sumbermujur Village, Lumajang. Based on the results of dental and oral screening conducted on elementary school children who were affected by the disaster, it was found that the OHI-S score was in the good criteria (0.8-1.06), but the DMF-T score was in the low criteria (1.52-2.5). to moderate (3.7), and the dmf-t score is included in the criteria of moderate (3.0-3.89) to high (4.8-4.87). The cause of the high incidence of dental caries in elementary school students is the lack of knowledge of elementary school students about oral health, which can be concluded from the wrong behavior or way of brushing their teeth and the right knowledge about when to brush their teeth. Efforts that can be made to improve this behavior are education which is included in promotive and preventive efforts.